Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có : (3x - 0.5) ( 2x + 2.5) = 0
\(\Leftrightarrow\orbr{\begin{cases}3x-0,5=0\\2x+2,5=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}3x=0,5\\2x=-2,5\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{0,5}{3}=\frac{1}{6}\\x=-\frac{2,5}{2}=\frac{5}{4}\end{cases}}\)
1)\(A=\left(\frac{1}{2}-1\right).\left(\frac{1}{3}-1\right).\left(\frac{1}{4}-1\right)....\left(\frac{1}{2008}-1\right).\left(\frac{1}{2009}-1\right)=\left(-\frac{1}{2}\right)\left(-\frac{2}{3}\right)...\left(-\frac{2008}{2009}\right)=\frac{1.2.3...2008}{2.3.4....2009}=\frac{1}{2009}\)
2)\(A=\frac{x-7}{2}\)
Do 2>0 =>A>0 <=>x-7>0<=>x>7
Vậy x>7 thì A>0
3)\(A=\frac{x+3}{x-5}\)
Do x+3>x-5 =>A<0<=>x+3>0 và x-5<0
<=>-3<x<5
Vậy -3<x<5 thì A<0
2.(x-1)-3.(2x+2)-4.(2x+3)=16
=>2x-2-6x-6-8x-12=16
=>2x-6x-8x-(2+6+12)=16
=>x.(2-6-8)=16+20=36
=>x.(-12)=36
=>x=-3
Vậy x=-3
\(2\left(x-1\right)-3\left(2x+2\right)-4\left(2x+3\right)=16\)
\(\Leftrightarrow2x-2-6x-6-8x-12=16\)
\(\Leftrightarrow\left(2x-6x-8x\right)+\left(-2-6-12\right)=16\)
\(\Leftrightarrow-12x-20=16\)
\(\Leftrightarrow-12x=36\)
\(\Leftrightarrow x=\frac{-36}{12}-3\)
x bằng mấy và x bằng mấy thế ?